NO BEAST SO FIERCE THE CHAMPAWAT TIGER AND HER HUNTER, THE FIRST TIGER CONSERVATIONIST - DANE HUCKELBRIDGE (LONDON WILLIAM COLLINS, 2019)
The deadliest animal of all time meets the world's most legendary hunter in a classic battle between man and wild. But this pulse-pounding narrative is also a nuanced story of how colonialism and environmental destruction upset the natural order, placing man, tiger and nature on a collision course.
Keywords: JIM CORBETT -- TIGER HUNTING -- KUMAON - INDIA